Effect of Lycopene Administration on the Antioxidant Status of Hypercholesterolemic Wistar Rats (Rattus Norvegicus) - Dewi, Vina Ariesta; Fransisca, Silvia; Leslie, Wiiliam; Alexander, Rico (Poltekkes Kemenkes Palu, 2024)
An imbalance between oxidants and antioxidants causes oxidative stress. Antioxidants such as vitamins C and E, known to prevent various diseases, can help reduce oxidative stress. The antioxidant lycopene in fruits can prevent carcinogenesis and atherogenesis. The objective of this study is to assess the impact of administering lycopene at doses of 0.36, 0.72, and 1.08 mg/day from tomato (Lycopersicum esculentum) fruit extract on the antioxidant levels (Vitamin C, E, and GPx) in hypercholesterolemic Wistar rats (Rattus norvegicus). The research methods of this study employ true experiment designs, LSD post hoc, control, and treatment groups. Experimentally, 28 rats with the Wistar strain were assigned to control and treatment groups. Hypercholesterolemic rats were fed high-fat, high-cholesterol with 0.35 ml/day cholesterol crystals. Vitamin C, vitamin E, and GPx levels were measured. The result of this study shows lycopene increased both vitamin C and E (P3 > P2 > P1 > P0). A post hoc LSDV statistical test of vitamin C, vitamin E, and GPX levels shows a significant difference (p = 0.00). The conclusion of this study found that administering a dosage of 0.36 mg/head/day of lycopene to those with high cholesterol levels benefits the body's antioxidant status, thereby improving the overall ability to counteract oxidative stress.